J/Psi-nuclear bound states - Tsushima, K.; Lu, D. H.; Krein, Gastão Inácio [UNESP]; Thomas, A. W. (Amer Physical Soc, 2011)
J/Psi-nuclear bound state energies are calculated for a range of nuclei by solving the Proca (Klein-Gordon) equation. Critical input for the calculations, namely the medium-modified D and D* meson masses, as well as the nucleon density distributions in nuclei, are obtained from the quark-meson coupling model. The attractive potential originates from the D and D* meson loops in the J/Psi self-energy in the nuclear medium. It appears that J/Psi-nuclear bound states should produce a clear experimental signature provided that the J/Psi meson is produced in recoilless kinematics.